Species Diversity and Population Structure of Opossum Shrimp and Paste Shrimps from Lower South of Thailand - Ramarn, Tueanta; Chusong, Jaruwan; Amornviriyachai, Vijittra; Nitiphan, Suphachai; Kasinan, Jintana (Burapha Science Journal, 2026)
Study on species diversity and population structure of Opossum shrimp and Paste shrimps from Lower south of Thailand. Samples were collected 4 times in January, March, October and December 2021, with local fishing gear (mesh size 2 mm.) and sledge net (mesh size 0.5 mm.). The results of the study revealed a total of 7 species of them arranged in 2 Orders, namely Order Decapoda and Order Mysida. Order Decapoda belonged to the Family Sergastidae. Only 1 genus of Sergestid was found, genus Acetes, with 2 species, Acetes indicus and Acetes sibogea. In Order Mysida, 6 species of mysid shrimps were found, classified in the family Mysidae in 3 subfamilies, namely, subfamily Erythroppinae (Erythrops minuta), subfamily Mysinae (Acanthomysis thailandica, Notacanthomysis hodgarti, Gangemysis assimilis, Mesopodopsis orientalis), subfamily Rhopalophthalminae (Rhopalopthalmus egregious). Five categories were found in population structure of the genus Acetes: juvenile, immature male, immature female, mature male and female, but differ in the proportion of each group, with Acetes japonicus found female immature is the most, while Acetes sibogea has the most female adult group.